A COMPARATIVE ANALYSIS OF AP CALCULUS AB AND MATH 231 AT THE UNIVERSITY OF WISCONSIN–MILWAUKEE - (:unkn) unknown (My University, 2025)
This study looks at how well the AP Calculus AB curriculum prepares students for college mathematics at the level of Calculus I or higher. It focuses on two main questions: (1) How the goals of AP Calculus AB compare to those of a college Calculus I course; (2) How closely AP Calculus AB matches with MATH 231 at The University of Wisconsin-Milwaukee. Recent changes to the AP Calculus AB exam, influenced by broader calculus reform efforts, aim to shift the focus from procedural steps to fostering deeper conceptual understanding among students. This study explores whether these changes have meaningfully aligned the AP curriculum with the rigor and expectations of college calculus.
Keywords: Mathematics